Teknologi Informasi dan Komunikasi: Solusi untuk Ketimpangan Pendapatan di Indonesia? - Nurul Siti Jahidah; Fauziyah Adzimatinur (Jurnal Media Informatika, 2025)
− This study aims to analyze the effect of information and communication technology on income inequality. Information and communication technology discussed in this study are ICT infrastructure, ICT usage, and ICT skills. The research method used is quantitative descriptive research with the dependent variable being the Gini index and the independent variables being the ICT-Development Index sub-indices including ICT infrastructure, ICT usage, and ICT expertise. The research data source is from the Central Bureau of Statistics publication. Panel data regression analysis was conducted in this study with cross section data of 33 provinces in Indonesia from 2018 to 2023. The results show that ICT usage has a significant negative effect on income inequality. While the other two variables, ICT infrastructure and ICT skills do not have a significant effect on income inequality.